PENGGUNAAN MODEL PEMBELAJARAN TAKE AND GIVE DENGAN MEDIA GRAFIS DALAM PENINGKATAN PEMBELAJARAN IPS TENTANG PERSIAPAN KEMERDEKAAN INDONESIA PADA SISWA KELAS V SDN 3 KEDUNGWINANGUN TAHUN AJARAN 2016/2017 - Arum, Winda Damar; Suyanto, Imam; Chamdani, Muhamad (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Take and Give Learning Model using Graphic Media in improving the Learning of IPS about the Preparation of Indonesia?s Independence Day for the Fifth Grade Students of SDN 3 Kedungwinangun in the Academic Year of 2016/2017. The objective of this research to improve the learning of IPS through the use of take and give learning model using graphic media. Subjects of the research were 21 students of the fifth grade of SDN 3 Kedungwinangun. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Data were analyzed using quantitative and qualitative descriptive eanalysis consisting of data reduction, data display, and drawing conclusion or verification. The conclusion of this research is the use of model take and give learning model using graphic media can improve the learning of IPS about the preparation of Indonesia?s independence day for the fifth grade students of SDN 3 Kedungwinangun in the academic year of 2016/2017.Keywords: take and give model, graphic media, learning of IPSAbstrak: Penggunaan Model Pembelajaran Take and Give dengan Media Grafis dalam Peningkatan Pembelajaran IPS tentang Persiapan Kemerdekaan Indonesia pada Siswa Kelas V SDN 3 Kedungwinangun Tahun Ajaran 2016/2017. Penelitian ini bertujuan meningkatkan pembelajaran IPS melalui penggunaan model pembelajaran take and give dengan media grafis. Subjek penelitian ini adalah siswa kelas V SDN 3 Kedungwinangun tahun ajaran 2016/2017 yang berjumlah 21 siswa. Penelitian tindakan kolaboratif ini dilaksanakan dalam tiga siklus yang terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data menggunakan tes, observasi, dan wawancara. Validitas data diuji menggunakan triangulasi sumber dan teknik. Analisis data menggunakan teknik analisis data kuantitatif dan kualitatif. Simpulan penelitian ini adalah melalui penggunaan model pembelajaran take and give dengan media grafis dapat meningkatkan pembelajaran IPS tentang persiapan kemerdekaan Indonesia pada siswa kelas V SDN 3 Kedungwinangun tahun ajaran 2016/2017.Kata kunci: model take and give, media grafis, pembelajaran IPS